A Leibnizean vision of the enlightened society - Święczkowska, Halina (Folia Philosophica, 2008)
The article is an attempt to present a 17th century vision of the programme of building the enlightened society proposed by Gottfried Wilhelm Leibniz. Inventorying of human knowledge and common access to it were one of his life aims. The condition of their realization was a rebuilt and reinforcement of the German language - largely weakened in the second part of the 17th century as a result of the French culture domination as a tool serving the purpose of discovery and archive of any human invention. The national language, though, as underlined in many places, fulfills its social and cognitive functions in the best ways. A Leibnizean project of building the enlightened society concerns, among other things, the society inhabiting the territories of the Great Empire of German Nation, but, indeed, it has a universal character too because Leibniz considered science, technology, development of new research tools the key to happiness and well-being of the whole mankind.